Rebooting Computing: The Road Ahead. - Conte, Thomas M.; DeBenedictis, Erik P.; Gargini, Paolo A.; Track, Elie (Computer (00189162), 2017)
The IEEE Rebooting Computing Initiative, proposed in 2012, has launched a 15-year technology roadmap to address escalating computing-performance pressures: stalled device-physics advances coupled with big data demands, novel machine-learning problems, and complex software paradigms. Potential solutions range from new transistor technology to quantum computing.